A Highly Ordered Hydrophilic–Hydrophobic Janus Bi‐Functional Layer with Ultralow Pt Loading and Fast Gas/Water Transport for Fuel Cells. Issue 1 (22nd August 2020) - Meng, Xiantao; Deng, Xiang; Zhou, Liusheng; Hu, Bin; Tan, Wenyi; Zhou, Wei; Liu, Meilin; Shao, Zongping
Abstract : One of the critical challenges that limit broad commercialization of proton exchange membrane fuel cells (PEMFC) is to reduce the usage of Pt while maintaining high power output and sufficient durability. Herein, a novel bi‐functional layer consisting of vertically aligned carbon nanotubes (VACNTs) and nanoparticles of Pt‐Co catalysts (Pt‐Co/VACNTs) is reported for high‐performance PEMFCs. Readily prepared by a two‐step process, the Pt‐Co/VACNTs layer with a hydrophilic catalyst‐loaded side and a hydrophobic gas diffusion side enables a PTFE‐free electrode structure with fully exposed catalyst active sites and superior gas–water diffusion capability. When tested in a PEMFC, the bi‐functional Pt‐Co/VACNTs layer with ultralow Pt loading ( 65 μgcathode cm −2 ) demonstrates a power density of 19.5 kW gPt cathode −1 at 0.6 V, more than seven times that of a cell with commercial Pt/C catalyst (2.7 kW gPt cathode −1 at 0.6 V) at a loading of 400 μgcathode cm −2 tested under similar conditions. This remarkable design of VACNTs‐based catalyst with dual functionalities enables much lower Pt loading, faster mass transport, and higher electrochemical performance and stability. Further, the preparation procedure can be easily scaled up for low‐cost fabrication and commercialization. Abstract : The design of ordered‐structure catalyst layer plays a key role in improving the performance of a PEMFC. Reported here is the successful synthesis of a Pt‐Co loaded vertically aligned carbon nanotube arrays, which exhibit superior performance with no additional MPL layer in the cathode due to the highly ordered layer structure and Janus hydrophilic/hydrophobic for enhanced gas–water diffusion capability.